Kinerja Kompor Gasifikasi Natural Draft Dengan Bahan Bakar Limbah Kayu Jati - Indra Hidayatul Mubarah; David Andrio; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The gasification stove is one of the technologies for converting biomass into thermal energy for cooking that energy saving and environmental friendly. The gasification stove can increase thermal efficiency up to twice and the energy relatively larger than biomass combustion with conventional methods. The objective of research is to study the effect of secondary air flow rates on the perfomance of the gasification stove. This research uses three units gasification stove with dimension outer cylinder of the stove 1(H1 = 30 cm, D1 = 17 cm); stove 2 (H2 = 30 cm, D2 = 20 cm) and stove 3 (H3 = 30 cm, D3 = 23 cm). While the fuel used is teak wood. To evaluating stove perfomance procedure WBT (water boiling test) was used with response variables: burning rates, thermal efficiency, and fire power. Color, height, flame temperature of the stove are including in evaluation of stove perfomance. The experimental result obtained burning rates is approximately 14.03 to 19.55 g/minutes. Thermal efficiency of the natural draft gasification stove is approximately 29.07% to 39.9%, with the highest efficiency is on the stove with cylinder outside the stove in 23 cm diameter. The natural draft gasification stove capable of producing up to 5.9 kWth thermal energy with the highest flame temperature reaches 940oC.Keywords: biomass, gasification, natural draft, stove, thermal efficiency.